Qu\~ao fechadas s\~ao as porteiras ministeriais? Filiaç\~oes e fracionamento partidário na burocracia política da esplanada (1999-2018) - Felix Garcia Lopez; Thiago Moreira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
In this paper, we discuss new data on party affiliations within ministries to characterize party-political appointments in high- and mid-level bureaucracy, from 1999 to 2018. We argue that party cleavages within these organizational structures are significant and, to analyze the variation between portfolios, we propose an intra-ministerial party fractionalization index. By pointing out that partisanship and fractionalization are different dimensions, and vary significantly between ministries, an implication of our argument is to highlight intra-ministerial partisan cleavages in the study of government functioning and the relationship between the federal executive and legislature. We also suggest that observing the political-party divisions in each ministry is an aspect neglected in the analysis of government processes and Brazilian coalition presidentialism, including the success in the relationship with the Legislative, besides being a key factor to identify characteristics and obstacles to good governance of federal public policies.
Keywords: D72; D73; 330; top-level bureaucracy; political appointments; patronage; coalition presidentialism; Federal Executive Branch